Extraction and Determination of Chloramphenicol in Meat Using 1-Butyl-3-methylimidazolium Chloride-K2HPO4 Aqueous Two-Phase System Coupled with HPLC - Jiang, D.Y.; Han, J.; Yu, C.L.; Li, Y.F.; Wang, L.; Yan, Y.S. (Asian Journal of Chemistry, 2013)
An ionic liquid-salt aqueous two-phase system (ILATPS) consisting of 1-butyl-3-methylimidazolium chloride ([C4mim]Cl) and K2HPO4, which is a simple, green and rapid sample pretreatment technique was used for the simultaneous separation, concentration and analysis of chloramphenicol (CAP) coupled with high-performance liquid chromatography. The influence factors on partitions of chloramphenicol were studied, including the types of ionic liquids and salts, the concentration of salt and chloramphenicol, temperature, pH and the volume of ionic liquid. In [C4mim]Cl-K2HPO4 ILATPS, the extraction efficiency of chloramphenicol increased with the volume of [C4mim]Cl increase and decreased with temperature increase. Under the optimal conditions, the average extraction efficiency of chloramphenicol in [C4mim]Cl-K2HPO4 ILATPS was up to 95 %. This method has been satisfactorily applied to the analysis of chloramphenicol in meat samples with the detection limit of 0.23 ng g-1 and relative standard deviation (RSD) of 1.27 % (n = 7). The recovery of chloramphenicol was 94.4-107 % from meat samples with a RSD of 0.38-1.47 %, showing that this method was satisfactory for the separation of antibiotics.